2013
DOI: 10.1111/chd.12127
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Subaortic Stenosis: A Clinical Dilemma for Clinicians and Patients

Abstract: Subaortic stenosis carries considerable morbidity and mortality. In most cases, patients have an underlying left ventricular outflow tract morphology that promotes turbulence at the outflow tract, which induces the development of subaortic fibromuscular tissue. A subset of patients will progress to develop severe stenosis and aortic regurgitation, but it has been difficult to determine which patients are at risk. While resection of the subaortic tissue improves immediate outcome, many patients have recurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
1
19
0
2
Order By: Relevance
“…Recommendations range from early operation to longer periods of observation, depending on patient characteristics. Ezon et al reported that ≥2 studies recommended surgery at diagnosis, regardless of the severity of the obstruction . Brauner et al suggested that early surgery prevents AR .…”
Section: Treatmentmentioning
confidence: 99%
“…Recommendations range from early operation to longer periods of observation, depending on patient characteristics. Ezon et al reported that ≥2 studies recommended surgery at diagnosis, regardless of the severity of the obstruction . Brauner et al suggested that early surgery prevents AR .…”
Section: Treatmentmentioning
confidence: 99%
“…The majority of interatrial communications can be divided anatomically into two groups: those located within the rims of the oval fossa, and those located outside the oval fossa [ 5 ]. The latter lesions include the sinus venosus, coronary sinus, and “ostium primum” defects.…”
Section: Discussionmentioning
confidence: 99%
“…The fibromuscular fixed subaortic stenosis is the most frequent, and in many cases the tunnel-type lesions are associated with a greater degree of stenosis. They are isolated or acquired and their prevalence in adults with congenital heart disease is 6.5%, with a male to female ratio of 2:1 [4][5][6][7]. We reported an interesting and reliable case of double orifice fixed subaortic membrane in adults.…”
Section: Introductionmentioning
confidence: 99%